(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Investigation on the structural relationship of information technology functional quality, customer value, technology used, risk perception and customer experience of banking customer satisfaction during covid19 pandemic is very important to provide significant benefits to increase the number of customers. This research design uses a quantitative approach through a questionnaire survey conducted on banking customers in Indonesia. Data analysis was performed using statistical software, namely LISREL Version 8.0. The results of the analysis show that functional quality, perceived customer value, technology use, perceived risk and customer experience have a significant relationship with banking customer satisfaction during the covid19 pandemic. In detail, the functional quality of banking technology is considered to have contributed 39% to customer satisfaction when implementing health protocols. Customer value contributes to customer satisfaction, technology used contributed to the customer satisfaction and perceived risk shaping customer satisfaction. In addition customer experience when implementing health protocols during the covid19 pandemic influence to customer satisfaction. In conclusion, functional quality, customer value, technology used, perceived risk and customer experience show the most significant contribution to banking customer satisfaction when implementing health protocols during the covid19 pandemic and create good acceptance of banking service performance from the aspects of empathy, physical evidence, reliability, fast response, time saving and cost-effectiveness and the new service development.